Breaking Patriarchal Gender Stereotype. Being A Female Rector of the Institut Seni Budaya Indonesia/ISBI Bandung, West Java, Indonesia - Nurmila, Nina (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2017)
Patriarchy is a system that put adult men in the central or the most important position, while women and children are put in relation to the interest of the patriarch (adult men). The over generalised belief (stereotype) of women in patriarchal system is that women are subordinate to men and be housewife who serves her husband, does houseworks and looks after her children. This paper will elaborate the case study of a couple who break this patriarchal gender stereotype, in which the husband flexibly changes his role to adapt and support his wifeâs career as the Rector of ISBI. This case study shows that not all men are patriarchal and that education can be a powerful tool to break patriarchal gender relation both in private and public spheres. Keywords : Gender stereotype, female leadership, Indonesian Islam, patriarchy